Cerebral activation pattern in primary writing tremor. Issue 6 (1st December 2000) - Berg, D; Preibisch, C; Hofmann, E; Naumann, M
Abstract : OBJECTIVE: To compare the cerebral activation pattern during writing of patients with writing tremor with healthy controls using functional MRI METHODS: Three patients with writing tremor and 10 healthy controls were examined using a 1.5 Tesla scanner. All subjects performed a paradigm of alternating 30 second periods of rest or writing. For functional imaging 60 EPI multislice data sets were acquired. All images were analyzed using SPM96 software. Data were analyzed for the group of patients with writing tremor and compared with those of the control group. RESULTS: Both patients with writing tremor and controls showed a significant activation of the contralateral primary sensorimotor cortex, SMA, and area 44. By contrast, motor cortex activation in writing tremor also included the contralateral premotor area (area 6) and ipsilateral prefrontal area (inferior frontal gyrus; areas 10, 44, and 47). Only patients with writing tremor showed a bilateral activation of the parietal lobule (area 40) with a more pronounced activation on the contralateral side. Furthermore, there was a bilateral activation of the cerebellum with a more pronounced area of activation on the ipsilateral side. CONCLUSIONS: Brain areas activated in writing tremor included activation patterns otherwise typical for both essential tremor and writer's cramp. Therefore a distinct category for writing tremor integrating hallmarks of essential tremor and writer's cramp is proposed.